Quillen’s theorem A through homology with local coefficients and Grothendieck spectral sequence - Tochi, Guillermo (2014)
Fil: Tochi, Guillermo. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.